Feature subset selection wrapper based on mutual information and rough sets - Foithong, Sombut; Pinngern, Ouen; Attachoo, Boonwat (My University, 2012)
In this paper, we introduced a novel feature selection method based on the hybrid model (filter-wrapper). We developed a feature selection method using the mutual information criterion without requiring a user-defined parameter for the selection of the candidate feature set. Subsequently, to reduce the computational cost and avoid encountering to local maxima of wrapper search, a wrapper approach searches in the space of a superreduct which is selected from the candidate feature set. Finally, the wrapper approach determines to select a proper feature set which better suits the learning algorithm. The efficiency and effectiveness of our technique is demonstrated through extensive comparison with other representative methods. Our approach shows an excellent performance, not only high classification accuracy, but also with respect to the number of features selected. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Feature selection; Multilayer perceptron (MLP) neural networks; Mutual information; Variable precision rough set model